2009
DOI: 10.24112/ajper.151770
|View full text |Cite
|
Sign up to set email alerts
|

Practice of the Beginning Secondary School Physical Education Teachers

Abstract: LANGUAGE NOTE | Document text in English; abstract also in Chinese. The purpose of the study was to investigate the practice of teaching of beginning secondary school physical education teachers. The problems and the factors that confronted the teachers in their first year of work were examined. Thirteen physical education graduates of the Hong Kong Institute of Education in 2005 teaching in secondary schools were purposely invited to participate in the study. Qualitative data were collected by a combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These researchers found that teachers advocate the use of written plans to help achieve focused and structured classes. However, other researchers have reported a lack of planning among physical educators (Cruz and Li, 2009;Graham, 2008). Specifically, Graham (2008) indicated that there are many physical education teachers who do not see planning as a necessity and do not enjoy making written plans, and consequently try to avoid developing written plans whenever possible.…”
Section: Planningmentioning
confidence: 99%
“…These researchers found that teachers advocate the use of written plans to help achieve focused and structured classes. However, other researchers have reported a lack of planning among physical educators (Cruz and Li, 2009;Graham, 2008). Specifically, Graham (2008) indicated that there are many physical education teachers who do not see planning as a necessity and do not enjoy making written plans, and consequently try to avoid developing written plans whenever possible.…”
Section: Planningmentioning
confidence: 99%